2022
DOI: 10.1038/s41598-022-15425-x
|View full text |Cite
|
Sign up to set email alerts
|

Early retinal functional alteration in relation to diabetes duration in patients with type 2 diabetes without diabetic retinopathy

Abstract: To examine the retinal structure and function in relation to diabetes duration and glycemia in patients without diabetic retinopathy (DR). 85 adults with type 2 diabetes without DR or macular edema underwent dilated indirect ophthalmoscopy, optical coherence tomography (OCT), ultra-wide field fundus photography, multifocal electroretinography (mfERG) and HbA1C assessment. Patients were stratified as those with diabetes duration < 10 years and ≥ 10 years. Right eyes of all participants were analyzed. mfERG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…High levels of HbA1c affect patients with T1DM by decreasing amplitude and increasing implicit time, while neither of these two variables are affected in patients with T2DM. The absence of alterations in mERG results in patients with T2DM is consistent with the studies of Srinivasan et al [ 25 ] and Santos et al [ 9 ], who studied 449 patients with T2DM recruited from the Open Consortium for the Early Treatment of Diabetic Retinopathy (EUROCONDOR). It is important, therefore, that our results for patients with T1DM show that high levels of HbA1c influence the mERG scores.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…High levels of HbA1c affect patients with T1DM by decreasing amplitude and increasing implicit time, while neither of these two variables are affected in patients with T2DM. The absence of alterations in mERG results in patients with T2DM is consistent with the studies of Srinivasan et al [ 25 ] and Santos et al [ 9 ], who studied 449 patients with T2DM recruited from the Open Consortium for the Early Treatment of Diabetic Retinopathy (EUROCONDOR). It is important, therefore, that our results for patients with T1DM show that high levels of HbA1c influence the mERG scores.…”
Section: Discussionsupporting
confidence: 89%
“…This could be explained by T1DM patients having amplitude values lower than T2DM patients, as shown in Table 2 , and having longer DM duration. Srinnivasan et al [ 25 ] studied a series of 85 patients with T2DM who had a DM duration of greater than 10 years and without DR. They reported a decrease in amplitude and an increase in implicit time compared to patients with DM duration of less than 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…However, after a one-year follow-up, these areas were found to be more susceptible to the development of microaneurysms compared to zones with a normal baseline implicit time [99]. In short, mfERG can be a valuable monitoring tool and effectively identify early abnormalities of the retina in DM patients without or with early stages of DR [100][101][102]. Notably, a mfERG study suggested that males may be more vulnerable to the neurodegenerative changes that preceded the development of background diabetic retinopathy in type 2 diabetes, compared to their female counterparts [103].…”
Section: Multifocal Electroretinogram (Merg)mentioning
confidence: 98%
“…OCT angiography (OCTA) is a rapid, noninvasive, and high-resolution ocular fundus examination that can simultaneously perform tomography scans and obtain blood flow information ( 11 , 12 ). The high resolution of OCTA can determine the occurrence of preclinical retinopathy, by, for example, identifying changes in the foveal avascular zone, as well as alterations in vessel density and retinal thickness ( 11 , 13 ). Although imaging by OCTA was previously limited to a 3 × 3 mm or 6 × 6 mm area in the center of the macula, this method can acquire high-resolution tomography and angiography images of 12 × 12 mm and even 24 × 20 mm areas of the retina and choroid using a single capture ( Figure 1 ) ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%